Specific immunotherapy and turning off the T cell: how does it work? - (:unkn) unknown (ELSEVIER SCIENCE INC, 2011)
Objective: To examine T-regulatory (Treg) cell functions in allergic immune responses and their roles during allergen specific immunotherapy based on recent developments and current understanding of immune regulation. Data Sources: PubMed search of English-language articles regarding Treg cells and allergen specific immunotherapy. Study Selection: Articles on the subject matter were selected and reviewed. Results: Allergen specific immunotherapy is the ultimate treatment modality targeting the immunopathogenic mechanisms of allergic disorders. A diminished allergen-specific T-cell proliferation and suppressed secretion of T(H)1- and T(H)2-type cytokines are the characteristic hallmarks. In addition, Treg cells inhibit the development of allergen-specific T(H)2 and T(H)1 cell responses and therefore exert key roles in healthy immune response to allergens. Treg cells potently suppress IgE production and directly or indirectly control the activity of effector cells of allergic inflammation, such as eosinophils, basophils, and mast cells. Conclusion: As advancements in the field of allergen specific immunotherapy ensue, they may provide novel progression of more rational and safer approaches for the prevention and treatment of allergic disorders. Currently, the Treg cell field is an open research area to increase our understanding in mechanisms of peripheral tolerance to allergens. Ann Allergy Asthma Immunol. 2011;107:381-392.
Keywords: ALLERGEN-SPECIFIC IMMUNOTHERAPY; IMMUNOLOGICAL SELF-TOLERANCE; GRASS-POLLEN IMMUNOTHERAPY; HISTAMINE H-4 RECEPTOR; TRANSCRIPTION FACTOR FOXP3; BEE VENOM IMMUNOTHERAPY; GROWTH-FACTOR-BETA; REGULATORY-CELLS; DENDRITIC CELLS; TGF-BETA